(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, we have compared the performance of IMABN-2 and MALN-2. To compare the performance, data packets were passed via both networks in faulty and non-faulty environments. Results show that MALN-2 performs better than the IMABN-2. Cost of IMABN-2 and MALN-2 is also compared with other existing MINs.